Theorizing criminality and policing in the digital media age - Wiest, Julie (Studies in media and communications ;, 2021)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS),this volume in Emerald' Studies in Media and Communications' features social science research on criminality, policing, and mass media in the digital age. Chapters offer empirically supported studies that expand on knowledge about new possibilities for crime and policing, representations of criminality via digital media, and methodological considerations for contemporary studies of crime and media. Criminality, policing, and mass media are enduring topics in studies of the social world, and scholarly advances in these areas are particularly pertinent in times of social and cultural change. The digital revolution that began in post-industrial societies has affected, to varying extents, most nations in the world, introducing new opportunities for crime commission and law enforcement, transforming social structures and organization, and altering norms and practices of social interaction. Each chapter offers empirically supported insights into the new and evolving landscape of criminality and policing. Scholars address emerging patterns and practices such as technologically mediated intimate partner violence, digitally altered pornography and its consequences, and algorithm-supported methods of policing; representations of criminals and law enforcement in international news and entertainment media; and research methods for studying crime and media in a changing world.